Game-Theoretic Analyses of Bargaining - Bishop, Robert L. (Quarterly Journal of Economics, 1963)
I. Characteristics of the game-theoretic approach, 559. — II. Theories of fixed-threat bargaining: Nach's theory, 563; the Zeuthen-Harsanyi theory, 566; Raiffa's theories, 569; a welfare theory, 572; further critique, 574. — III. Theories of variable-threat bargaining: an illustrative duopoly situation, 582; Nash's theory, 589; a Shapley theory, 593; Raiffa's theories, 594; Braithwaite's theory, 595; other theories, 597; Critical evaluation, 599. — IV. Conclusion, 602.